Mini-pillar array for hydrogel-supported 3D culture and high-content histologic analysis of human tumor spheroids. Issue 12 (19th May 2016) - Kang, Jihoon; Lee, Dong Woo; Hwang, Hyun Ju; Yeon, Sang-Eun; Lee, Moo-Yeal; Kuh, Hyo-Jeong
Abstract : Three-dimensional (3D) cancer cell culture models mimic the complex 3D organization and microenvironment of human solid tumor tissue and are thus considered as highly predictive models representing avascular tumor regions. Abstract : Three-dimensional (3D) cancer cell culture models mimic the complex 3D organization and microenvironment of human solid tumor tissue and are thus considered as highly predictive models representing avascular tumor regions. Confocal laser scanning microscopy is useful for monitoring drug penetration and therapeutic responses in 3D tumor models; however, photonic attenuation at increasing imaging depths and limited penetration of common fluorescence tracers are significant technical challenges to imaging. Immunohistological staining would be a good alternative, but the preparation of tissue sections from rather fragile spheroids through fixing and embedding procedures is challenging. Here we introduce a novel 3 × 3 mini-pillar array chip that can be utilized for 3D cell culturing and sectioning for high-content histologic analysis. The mini-pillar array chip facilitated the generation of 3D spheroids of human cancer cells within hydrogels such as alginate, collagen, and Matrigel. As expected, visualization of the 3D distribution of calcein AM and doxorubicin by optical sectioning was limited by photonic attenuation and dye penetration. The integrity of the 3D microtissue section was confirmed by immunostaining on paraffin sections and cryo-sections. The applicability of the mini-pillar array for drug activity evaluation was tested by measuring viability changes in spheroids exposed to anti-cancer agents, 5-fluorouracil and tirapazamine. Thus, our novel mini-pillar array platform can potentially promote high-content histologic analysis of 3D cultures and can be further optimized for field-specific needs.